2017
DOI: 10.1002/hon.2437_54
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Pd‐1 Checkpoint With Anti–pd‐l1 Antibody Avelumab Is Sufficient for Clinical Activity in Relapsed/Refractory Classical Hodgkin Lymphoma (Chl)

Abstract: significant difference between ABVD and AVD, RT or no RT, presence or absence of a residual mass, or PET score (1-3). The remaining 39 pts with bulky stage II HL and a positive PET2 received BEACOPP. Of the 11 patients receiving RT, there was just 1 progression, despite only 5 reaching conventional CT based CR or CR(u). Conclusion:With longer follow-up, these RATHL results confirm that the primary study endpoint has been met, reliably excluding a 5% inferior 3 year PFS following de-escalation after a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Advanced Stage Classical Hodgkin's Lymphoma trial (NCT02603419), avelumab is being evaluated in patients who are not eligible for transplant or whose disease has relapsed after either AHCT or allo-HCT. 60 The ORR for all patients was 54.8%, with 2 CR (6.5%) and 15 PR (48.4%), including the 8 patients after allo-HCT, described in more detail later. In the preliminary results, 36.7% had grade 3 or higher treatmentrelated AEs.…”
Section: In the Phase 1 Avelumab In Patients With Previously Treatedmentioning
confidence: 86%
See 1 more Smart Citation
“…Advanced Stage Classical Hodgkin's Lymphoma trial (NCT02603419), avelumab is being evaluated in patients who are not eligible for transplant or whose disease has relapsed after either AHCT or allo-HCT. 60 The ORR for all patients was 54.8%, with 2 CR (6.5%) and 15 PR (48.4%), including the 8 patients after allo-HCT, described in more detail later. In the preliminary results, 36.7% had grade 3 or higher treatmentrelated AEs.…”
Section: In the Phase 1 Avelumab In Patients With Previously Treatedmentioning
confidence: 86%
“…Finally, avelumab produced a 75% ORR in a phase 1 study with 8 patients, with 2 patients developing grade 3 liver GHVD, which resolved with treatment. 60 An additional important consideration for allo-HCT is the availability of a donor. In recent years, several studies have evaluated or reviewed the use of haploidentical donors and found encouraging results.…”
Section: Considerations For Allo-hctmentioning
confidence: 99%
“…3,4 PD-L1 and PD-1 inhibitors have shown excellent results in treatment relapse/refractory cHL patients. [5][6][7] CTLA-4 has long been recognized for its regulatory function, potentially decreasing antitumor immune response. Improvement of the immune response via CTLA-4 blockade significantly increases the survival of patients with metastatic melanoma.…”
mentioning
confidence: 99%
“…Avelumab is a fully human IgG1 monoclonal antibody that selectively binds to PD‐L1 (Boyerinas et al , ). Early results from a phase I study of avelumab in patients with R/R HL demonstrated a 42% ORR among 31 patients, including a 16% CR rate (Chen et al , ,b). Thus, anti‐PD‐L1 therapy is also a promising strategy in HL.…”
Section: Antibody‐based Therapiesmentioning
confidence: 99%